Impact of wallet cards compared to conventional chemotherapy education in patients with newly-diagnosed cancer. Issue 28 (1st October 2022) - Bhargava, Anika; Jain, Nikita; Rojan, Adam; Ngo, Phuong; Dong, Brian
Abstract : 363 Background: According to American Cancer Society, 1.9 million new cases of cancer were diagnosed in year 2021, majority of who will undergo chemotherapy (1). With these treatments, there is often an overwhelming amount of information given to patients. We will first assess the percentage of new cancer patients that can recall their cancer treatments with the current patient education format. We then aim to improve patient understanding of their treatment with the introduction of a chemotherapy wallet card. Methods: This is a single center prospective cohort study at the University of Louisville, Brown Cancer Center. In phase one 50 new patients will be recruited from various oncology clinics who will receive conventional verbal chemotherapy education. On cycle two of their treatment, we will administer a survey (figure 1) to assess their understanding of their regimen. In phase two we will recruit 50 new patients and introduce a chemotherapy wallet card filled by the pharmacist to be given during their chemotherapy education and administer the survey on cycle two. We will then compare these two populations to evaluate the impact of the chemotherapy wallet cards. Results: Preliminary results from the first phase have been obtained of 15 newly diagnosed cancer patients. Surveys obtained on cycle two revealed 100% patients correctly identified their cancer diagnosis and 60% were able to correctly name their chemotherapy regimen. 53% of patients were able to identify three correct treatment side effects. Conclusions: Preliminary results show 60% of patients have suboptimal identification of their chemotherapy regimens. Previous studies have shown many patients will visit the emergency department in their first year of treatment. This is of concern as patients may not be able to provide accurate information of their current treatment to these providers resulting in suboptimal care. Our goal will be to see if chemotherapy wallet cards will help to increase patient knowledge and improve patient quality of care.Survey to assess level of cancer treatment awareness. Chemotherapy Survey 1. Please list the type of cancer you are receiving treatment for 2. Please list the names of the treatments you are currently receiving for your cancer 1.2.3. 3. List three side effects of the cancer treatment you're receiving? 1.2.3. 4. Please circle the highest level of education you have completed Didn't finish High school High school College Graduate Degree 5. Who do you feel comfortable receiving chemotherapy education from? Oncologist Oncology Nurse Pharmacist Brochures Internet 6. Do you find it difficult to look up information about cancer treatments? YES NO 7. Would you be interested in online videos to tell you about your cancer treatments? YES NO 8. Would you be interested in a mobile application to reference your cancer records? YES NO References American Cancer Society. Cancer Facts & Figures 2021. Atlanta; 2021.